Concept and model for measurement of sustainability of village credit institutions (study on LPD Kedonganan, Bali) - Wilyadewi, Ida I Dewa Ayu Yayati; Trarintya, Mirah Ayu Putri; Wulandari, Ni Luh Adisti Abiyoga; Abiyoga VS, Ni Nyoman Adityarini; Purwaningrat, Putu Atim (Enrichment : Journal of Management, 2023)
Village Credit Institutions (LPD) as microfinance institutions belonging to traditional villages are an important part in realizing and driving a traditional village economy based on local wisdom in Bali. The role of LPD is not only seen from its ability to create a healthy LPD but also its benefits for the community in each traditional village. LPDs that are in a healthy condition are expected to be able to realize business sustainability as demonstrated by the ability to realize sustainability through concepts and measurements. This research aims to produce a concept and measurement model for LPD sustainability, seen from the dimensions of Economic Sustainability, Social Sustainability and Environmental Sustainability. This research was carried out with a qualitative approach, by taking LPD Kedonganan as the research location because LPD Kedonganan is in the healthy category as a requirement for Sustainability and LPD Kedonganan has been able to realize its benefits for improving community welfare (social), its ability to manage finances and achieve profitability (economy), and its ability to preserve and develop traditional villages (environment) through activities based on local wisdom. Data collection in this research was carried out through in-depth interviews, then analyzed using descriptive narrative. The research results show that the concept and measurement of Sustainability is an interpretive concept with various views by researchers, but almost all of it involves three dimensions of Sustainability, namely Economic Sustainability, Environmental Sustainability, and Social Sustainability. The indicators or measurement dimensions refer to the activities in measuring the organization's sustainability SustainabilityLPD can be measured using three dimensions, namely the economic dimension, the environmental dimension and the social dimension which results in a LPD Sustainability measurement formulation.